2015
DOI: 10.1007/s00221-015-4220-1
|View full text |Cite
|
Sign up to set email alerts
|

Kinaesthetic mirror illusion and spatial congruence

Abstract: Position sense and kinaesthesia are mainly derived from the integration of somaesthetic and visual afferents to form a single, coherent percept. However, visual information related to the body can play a dominant role in these perceptual processes in some circumstances, and notably in the mirror paradigm. The objective of the present study was to determine whether or not the kinaesthetic illusions experienced in the mirror paradigm obey one of the key rules of multisensory integration: spatial congruence. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 32 publications
4
23
0
Order By: Relevance
“…An illusion of movement is generated in a hidden, stationary arm by watching a mirror image of the other, moving arm (Metral et al . ). The subject falsely interprets the mirror image as being their hidden arm.…”
Section: Discussionmentioning
confidence: 97%
“…An illusion of movement is generated in a hidden, stationary arm by watching a mirror image of the other, moving arm (Metral et al . ). The subject falsely interprets the mirror image as being their hidden arm.…”
Section: Discussionmentioning
confidence: 97%
“…It must also be borne in mind that masking the afferent signals from the antagonistic muscles of the arm subjected to the illusion has exactly the opposite effect; the mirror illusion occurred earlier (with reduced latency) and more intensely (with a higher perceived speed) than in the absence of proprioceptive masking (Guerraz et al 2012). Similarly, Metral et al (2015) showed that a larger degree of spatial incongruence between the mirror arm and the somaesthetically specified position of the unseen arm subjected to mirror illusion(with a shift of between 0° and 90° in the sagittal plane) was associated with a less intense kinaesthetic illusion. Finally, the illusory displacement can be either strengthened or weakened by adding proprioceptive inputs through vibration of the antagonist or agonist muscles of the hidden arm respectively (Guerraz et al 2012, Tsuge et al 2012.…”
Section: Limited Vision Of the Arm Provides Sufficient Kinaesthetic Cmentioning
confidence: 99%
“…The mirror paradigm was initially developed to treat phantom limb pain in unilateral amputees (Ramachandran et al 1995) but hasalso been used over the last two decadesas a rehabilitation tool for promoting recovery from hemiparesis (RamachandranandAlthschuler2009; RosenandLundborg2005; Dohle etal.2009;Guerraz 2015). More recently, experiments conducted in healthy participants showed that mirror reflection of an arm moved passively by a motorized manipulandum induces consistent, vivid kinaesthetic illusions of movement of the hidden, static arm in the direction of the mirror displacement (Guerraz et al 2012;Tsuge et al 2012;Metral et al 2015). The occurrence of this visually induced kinaesthetic illusion indicates that visual afferents might be of prime importance in sensing limb movement (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mirror illusion can be induced by simply placing the limbs in the mirror context (Holmes & Spence, 2005, Holmes et al, 2006; Snijders et al 2007), other studies have required that participants perform cycles of synchronous bimanual movements prior to engaging in the main reaching task (e.g., Guerraz et al, 2012; Holmes, Crozier, & Spence, 2004; Holmes & Spence, 2005; Metral et al, 2015). One study (Holmes & Spence, 2005) showed that the magnitude of the illusion (1) was stronger when preceded by active bimanual movement than passive viewing without movement and (2) increased incrementally as the duration of bimanual movement increased (4, 8, or 12 seconds).…”
Section: The Mirror Illusion and The Body State Estimatesmentioning
confidence: 99%